Effect of integrated nutrient management in rice on vegetative growth and economic profitability of wheat under long term rice wheat cropping system - Ranjan, Shivani; Kumar, Sanjay; Dutta, Swaraj Kumar; Sow, Sumit; Ghosh, Mainak (Journal of Cereal Research, 2022)
The study investigated the effect of variable integrated nutrient management (INM) in rice and inorganic nutrient management in wheat on vegetative growth and economic profitability of wheat. The results revealed that growth parameters such as plant height (100.4 cm), LAI (2.43) at maturity and number of tillers/m 2 (377) were observed highest with 50% recommended dose of fertilizers (RDF) and 50% N (nitrogen) through farm yard manure (FYM) in rice and 100% RDF in wheat. Similarly, highest biomass yield of 10.37 t ha -1 was recorded with application of 50% RDF and 50% N through FYM in rice and 100% RDF in wheat. A highly positive and significant correlation was observed between plant height and number of tillers/m 2 with biomass yield. Net return (69795 ₹ ha -1 ) and B:C ratio of 1.88 were also recorded highest with application of 50% RDF and 50% N through FYM in rice followed by 100% RDF in wheat. Thus, substitution of 50% inorganic N by FYM and application of 50% RDF in rice followed by 100% RDF in wheat was found useful to obtain the better growth and net return of wheat.